A Case Report of Median Nerve Entrapment in a Supracondylar Humeral Fracture: Diagnosis, Treatment, and Results After 5 Years of Follow-Up - Carlo Colonna; Joil Ramazzotti; Francesco Locatelli; Alessandro Crosio; Pierluigi Tos (Reports)
Background and Clinical Significance: Neurological complications in extension-type-III supracondylar humeral fractures (SCHFs) in children represent 11% of cases. An extension-type-III SCHF with posterolateral displacement of the distal fragment is commonly associated with damage to the median nerve and the anterior interosseous nerve (AIN). Neurological complications are often unnoticed, and their immediate postoperative diagnosis is difficult, particularly in young children. Neurapraxia, the most common complication, usually undergoes spontaneous nerve recovery. Case Presentation: We report a case of a 7-year-old patient with postoperative median nerve palsy after an SCHF (Gartland type III) who was referred to our unit from another hospital due to a lack of spontaneous recovery. In addition, motor and sensory functions were absent. As ultrasound (US) indicated nerve kinking at the fracture site, an exploration was performed. The nerve was trapped within the fracture and the callus. It was surgically extracted, and intraoperative examination with US indicated that resecting the kinked nerve, freeing the two stumps, and attempting a primary end-to-end suture represented the best course of action. We present this case with a 5-year follow-up surgery, which showed a good clinical outcome. Conclusions: This case is noteworthy because of its diagnostic and therapeutic pathways, and it is complemented by surgical and ultrasound images that can assist other surgeons in similar circumstances.